CONTINGENCY ANALYSIS OF POWER SYSTEM NETWORKS - ABDUL RAUF, MOHD HAFIZ (Universiti Teknologi Petronas, 2006)
In this modern power system, planning and construction of the system with outage minimization as a major design criterion is becoming more important. However, even with the best possible construction and operating practices, outages still can occur. Several techniques have been developed to analyze the status of the system after the real outage occurs. This project presents an alternative way of conducting power flow analysis in determining the new bus voltages and line currents during outage occurrence. The algorithms have been accommodated in one complete program making it an effective tool for contingency analysis. The program has been tested on an IEEE bus test case and the remarkable results obtained in terms of its reduced computation time and accuracy showed that this technique could be implemented, particularly when involving practical work with a lot of calculations.